Process Simulation and Economic Analysis of Pre-combustion CO2 Capture With Deep Eutectic Solvents - Xin, Kun; Hashish, Mahmoud; Roghair, Ivo; van Sint Annaland, Martin (Frontiers in Energy Research, 2020)
The purpose of this paper is to identify firstly the most important solvent characteristics in the CO2 capture process and secondly to determine how they contribute to the total cost of CO2 separation and analyze the economic feasibility of current deep eutectic solvents (DESs) in literature. A rate-based modeling approach was adopted to simulate pre-combustion CO2 capture. The effects of the flow model and the number of segments were investigated for the Selexol process. Different mass transfer correlations due to Bravo et al. (1985), Billet and Schultes (1993) and Hanley and Chen (2012) were adopted for the rate-based models and compared with the equilibrium modelling approach. Subsequently, property and process models were developed for a mixture of decanoic acid and menthol, in equal quantities. A physical property study was conducted with this DES. The CO2 solubility is found to be very important in all rate-based models, as expected, but properties such as the surface tension, thermal conductivity, heat capacity and volatility had a minor influence on the absorption performance. The solvent viscosity strongly affects the mass transfer rate when using the Hanley and Chen (2012) correlations, whereas it plays only a small role in the other two sets of correlations. Using a high CO2 solubility as criterion, two mixtures of allyl triphenylphosphonium bromide (ATPPB) and diethylene glycol (DEG) were screened out from literature. The conventional Selexol process was set as the benchmark for the evaluation of the performances of these DESs. The optimum capture cost for Selexol process is 27.22, 26.66 and 30.84 $2018/tonne CO2 for the adopted correlations, respectively. ATPPB + DEG (1:4 molar ratio) can outperform Selexol when using the first two rate-based models, but not when applying the Hanley and Chen (2012) correlations. In this case a higher absorption temperature and absorber packing height can help reducing the capture cost for the more viscous DESs. The current mass transfer correlations need to be further improved and validated to more accurately describe the absorption rate in viscous solvents.